Development of Competitive mRNA PCR for the Quantification of Interleukin-6-Responsive junB Oncogene Expression - P. Igaz; G. Fejér; C. Szalai; S. Tóth; A. Falus (BioTechniques)
The transcription factor junB belongs to the jun family of protooncogenes. The appearence of junB mRNA in hepatic cells is an extremely early and sensitive marker of the action of proinflammatory cytokines including interleukin-6. In this study, a competitive reverse transcription (RT)-PCR assay has been developed that is suitable for the quantitative determination of junB mRNA expression. This nonisotopic assay compared to other methods (e.g., Northern blot) is a fast and convenient way to determine the expression of the junB gene and thus the immediate concentration- and time-dependent action of interleukin-6. Because interleukin-6 and interleukin-6-type cytokines play a highly important regulatory role in various pathophysiologically important processes, such as hepatic acute-phase reaction, the quantitative assay of junB mRNA completes the scale of laboratory approaches in inflammation and among other pathological conditions.